Fortification of Plain Cracker With Fish Flour - Iwan Yusuf B. Lelana; Lupi Purnomosari; Amir Husni (Indonesian Food and Nutrition Progress, 2003)
Fortification of plain crackers with Java tilapiaflour to increase protein was conducted. Completely Randomized Design with five treatments was applied. The treatments were dough without fish flour addition as control, addition with 5%, 10%, 15%, and 20%, they were replicated four times The crackers were measured for crude protein content, relative volumetric expansion and sensory properties. Results indicated that protein content in the crackers was increased proportionally with fish flour addition, but relative volumetric expansion, crispiness and consumer acceptance decreased. Addition of 5% fish flour is acceptable to consumers. Preparation to improve fish flour color and the use of agent to improve the sensory properties of the crackers are necessary.